2012
DOI: 10.1111/j.1365-2958.2012.08158.x
|View full text |Cite
|
Sign up to set email alerts
|

The linker sequence, joining the DNA‐binding domain of the homologous transcription factors, Mlc and NagC, to the rest of the protein, determines the specificity of their DNA target recognition in Escherichia coli

Abstract: Summary Protein–DNA recognition is fundamental to transcriptional regulation. Transcription factors must be capable of locating their specific sites situated throughout the genome and distinguishing them from related sites. Mlc and NagC control uptake and use of the sugars, glucose and N‐acetylglucosamine. Both their helix–turn–helix motifs and their consensus binding sites on DNA are very similar. One distinguishing feature is that most NagC sites have a C/G bp at positions −11 and +11 from the centre of symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 59 publications
(115 reference statements)
5
23
0
Order By: Relevance
“…Typically, E. coli NagC and Mlc proteins bind to DNA through a ‘TT‐9 bp‐AA’ motif; in the central 9‐bp region, there is a very strong preference for ‘CGCGNCGCG’ (Plumbridge, ; Brechemier‐Baey et al ., 2012; 2015). However, these characteristics are not conserved in PrpoS or UPbosR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, E. coli NagC and Mlc proteins bind to DNA through a ‘TT‐9 bp‐AA’ motif; in the central 9‐bp region, there is a very strong preference for ‘CGCGNCGCG’ (Plumbridge, ; Brechemier‐Baey et al ., 2012; 2015). However, these characteristics are not conserved in PrpoS or UPbosR.…”
Section: Resultsmentioning
confidence: 99%
“…BadR contains only two residues (G153 and H243) conserved in the NagC or XylR SDGs, supporting our conclusion that BadR probably does not bind specifically to GlcNAc‐6P or Xylulose‐5P (our EMSA data revealed that the binding of rBadR to PrpoS or UPbosR was not affected by phosphorylated sugars such as GlcNAc‐6P, Glucose‐6P and xylulose‐5P). Third, PrpoS or UPbosR does not contain a NagC or XylR binding consensus sequence (Jacob et al ., ; Stulke and Hillen, ; Brechemier‐Baey et al ., 2012; 2015). Finally, expression of GlcNAc metabolic genes such as nagA and nagB was not affected in a badR mutant (Miller et al ., ), implying that BadR does not act as bacterial NagC protein.…”
Section: Discussionmentioning
confidence: 99%
“…The nagR and gamR ORFs were amplified from chromosomal B. subtilis DNA with the pairs of oligonucleotides, Yvo1NdeI–Yvo2H6BamHI and Ybg1NdeI–Ybg2H6BamHI and inserted into pJES307 (an IPTG‐inducible T7 RNA polymerase based vector, Bréchemier‐Baey et al ., ) using the restriction sites included in the 5′ ends of the oligonucleotides. Oligonucleotide sequences are given in http://onlinelibrary.wiley.com/doi/10.1111/mmi.12544/suppinfo.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA fragments examined by DNase I footprinting were made by PCR in which one of the oligonucleotides had been previously labelled with [γ-32 P]-ATP and T4 polynucleotide kinase. DNase I footprinting was carried out as described (Bréchemier-Baey et al, 2012). The binding buffer was 25 mM HEPES, 100 mM K glutamate pH 8.0 containing 0.5 mg ml −1 BSA.…”
Section: Dnase I Footprinting and Combined Emsa And Dnase I Footprintingmentioning
confidence: 99%
“…In support of this hypothesis, Mlc has nine in-frame YafQ cleavage sites and no DinJ binding motifs so it is very likely the Mlc mRNA is degraded by YafQ. Also, Mlc is a ROK family transcriptional regulator that binds DNA via a helix-turn-helix motif and regulates glucose transport via its regulation of the phosphotranserase system [56]. In agreement with our hypothesis that Mlc may play a role regulating the activity of YafQ, mlc is induced during cold shock [57].…”
Section: Discussionmentioning
confidence: 99%